GOOD PRACTICES IN ADAPTED PHYSICAL ACTIVITY AT SOME BULGARIAN GENERAL SCHOOLS - Boyanka Peneva (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2008)
Early or late, quick or slow, world tendencies in education reach everyone country and start to master its social systems. Last two decades are time when special attention to people with disabilities is paid. As if it is the third step in equalizing the education. The first two steps are equalizing on base of race and gender. Speaking about pupils with disabilities 30 years ago PE specialists under stood only pupils with obesity. To day things changed radically. To the group of pupils with special educational needs can be related handicapped children with mild to moderate physical or psychic damages but also pupils with accelerated abilities in one or another sphere of knowledge or skills. To all of them teachers must of fer adequate and developing education but all this within main stream school. Individual and differentiate approach is unavoidable. The aims and goals of education should be the same for all pupils. So, main stream teachers should assume responsibility for meeting these special needs of their pupils. The problem is new for them, so they still feel them selves slightly confused but always seeking ways for best solving concrete situations. This refers even to teachers that have of many years experience in kinesitherapy. Practice in Bulgaria show that even obligatory instructions from the side of the ministry of education can not always help solving the problems. Our paper is an attempt to show some decisions of PE teachers from Sofia with pupils that need special education.